2018
DOI: 10.1002/clc.23026
|View full text |Cite
|
Sign up to set email alerts
|

Non‐coronary predictors of elevated high‐sensitive cardiac troponin T (hs‐cTnT) levels in an unselected emergency patient cohort

Abstract: Background Aim of this study was to evaluate the predictors of hs‐cTnT in a non‐ACS patient cohort admitted to the emergency department. Hypothesis Atrial fibrillation and hypertension may not always be sufficient for elevation for hs‐cTnT. Methods We performed a retrospective, single center study encompassing in total 1003 patients. Individuals were retrospectively divided in ACS‐ and non‐ACS patients by two independent investigators reviewing the medical records. In order to identify predictors of hs‐cTnT el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the literature, two studies also showed that the set of clinical-instrumental variables had the best capabilities of predicting an ACS diagnosis, although no data regarding cTn were reported [26,27]. On the other hand, other studies aimed to evaluate which factors were associated with an increase in hs-cTnT value and for this reason they differ from ours [28,29]. To the best of our knowledge, only Alcalai et al [30] attempted to determine which were the clinical-laboratory predictors of ACS in the presence of abnormal hs-cTnT values, and for these characteristics, our study may be partially similar.…”
Section: Discussionmentioning
confidence: 81%
“…In the literature, two studies also showed that the set of clinical-instrumental variables had the best capabilities of predicting an ACS diagnosis, although no data regarding cTn were reported [26,27]. On the other hand, other studies aimed to evaluate which factors were associated with an increase in hs-cTnT value and for this reason they differ from ours [28,29]. To the best of our knowledge, only Alcalai et al [30] attempted to determine which were the clinical-laboratory predictors of ACS in the presence of abnormal hs-cTnT values, and for these characteristics, our study may be partially similar.…”
Section: Discussionmentioning
confidence: 81%
“…These non-ACS troponin elevations can be related to cardiac causes (such as acute myocarditis, stress (Takotsubo) cardiomyopathy, tachycardia, or dilated cardiomyopathy) or due to noncardiac causes (such as trauma, exertion, chronic kidney disease, anemia, sepsis, or pulmonary embolism). [ 2 8 9 ]…”
Section: Introductionmentioning
confidence: 99%